First you need to replace all of the letter A's with -6 and all of the B's with 2.
The equation would look like this
2(-6)^2+5(2)^2
Second, you solve what in is the parenthesis 2(-6)=-12 5(2)= 10
Third, you rewrite the problem. -12^2+10^2
Fourth, you need to figure out what the final answer would be.
-12^2=-144 and 10^2=100
The answer would be -144+100=-44
Sorry!!! This is probably Wrong, I didn't use an algebra calculator or anything to check the answer. I didn't remember if I needed to bring the number in parenthesis to the power before or after multiplying.